The Role of Islamic Education Teachers in Shaping Students’ Character After the Implementation of the Merdeka Curriculum at Junior High Schools in Rantau Selamat District - Siti Aisyah; Zainal Abidin; Fakhrurrazi Fakhrurrazi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The objective of this study is to investigate the role, methodologies, effects, and challenges faced by Islamic Religious Education (IRE) teachers in influencing student character subsequent to the adoption of the Independent Curriculum in junior high schools within Rantau Selamat District. Utilizing a qualitative field research approach, data were gathered from school administrators, IRE teachers, and vice principals for curriculum through observations, interviews, and recording. The results show that IRE instructors play a planned role in teaching religious principles, discipline, responsibility, and tolerance through structured activities such congregational prayers, Qur'anic recitation, religious mentoring, and encouraging respect for others. Character education techniques stress learning by doing, like doing community work, keeping the school clean, taking part in Islamic festivities, and using rewards and punishments to teach discipline. These efforts have had an effect on both individuals and institutions. For example, students have shown positive changes in their behavior, and schools have seen their religious culture grow stronger through regular tadarus, communal worship, Friday charity programs, and the creation of Islamic spiritual organizations (ROHIS). Character development initiatives encounter obstacles, particularly constrained instructional time and inadequate backing from students' familial and societal contexts.